Programa de Habilidades Sociais com pais e professores: efeitos sobre educadores e crianças escolares - Casali, Ivana Gisel (2019)
The literature points out the importance of social skills for the quality of interpersonal relationships, being learned, from a young age, in the interaction with other people. Children with an elaborate repertoire of social skills exhibit fewer behavioral problems and better academic performance, having more favorable perspectives in the future. When favorable, the educational practices of parents and teachers in the school and family environment are indicated as protective factors of the child development, minimizing or neutralizing risk factors. These practices should be based on a repertoire of general and educational social skills of these educational agents. However, there are still insufficient programs aimed at promoting this repertoire and, in particular, the systematic study of its impacts on the Brazilian population. Based on this, the present study had as main objective to evaluate a Social Skills Program for parents and teachers of school children, examining their effects: (1) direct, on the social repertoire of the agents education; and (2) indirect, on children in terms of social skills, behavioral problems and academic performance. After a pilot study, the program for teachers were conducted, with 18 sessions of 75 minutes in weekly frequency and the program for parents, with 17 sessions of 90 minutes, also weekly. Thirty parents, eight teachers and their children/students (N = 35) participated in four groups, one non-intervention control (CG) and three experimental groups: EG1, involving parents and teachers; EG2, teachers only; and EG3, only parents. The children's repertoire was evaluated through the Social Skills Assessment System (SSRS-BR2) and the School Performance Test (TDE); and parents e teachers was evaluated through the Social Skills Inventory (IHS-Del-Prette), Inventory of Educational Social Skills (IHSE-Parents and IHSE-Teachers) and the Parental Assessment Protocol (PAP). Statistical analyzes showed effects: (1) direct on the social repertoire of parents and teachers who participated in the sessions, when compared to the control group; and (2) indirectly on the repertoire of social skills and academic performance, greater for EG1 children, who benefited from the involvement of parents and teachers in the program. Among the teachers, there was a statistically significant change between pre and postintervention (cultivate affection, support and good mood) and a significant late effect in the follow-up in the global social skills score and in specific factors (self-defense assertiveness; affective-sexual assertiveness; reprove, restrict and correct behaviors). Among the parents, there were statistically significant differences between pre and post intervention in the global scores of social skills and educational social skills and in specific factors (assertiveness of social self-exposition; affective-sexual assertiveness; establish limits, correct and control; talk/dialogue). Finally, those children whose parents and teachers participated in the program (EG1) showed, after the intervention, a significant improvement in the overall score of self-rated social skills and academic performance and in specific indicators (assertiveness, assertiveness and social entrepreneurship; writing). The results suggest the effectiveness of the program and the importance of investing in the planning of interventions in the family and school environment as a way to contribute to the social-emotional development of schoolchildren, even as indirect targets of intervention. Programs that include triadic intervention, frequent in international research, and that advance the limitations pointed out in the present study could provide even more robust results in the area.